2006
DOI: 10.1039/b511966a
|View full text |Cite
|
Sign up to set email alerts
|

A novel heterocyclic atom exchange reaction with Lawesson's reagent: a one-pot synthesis of dithiomaltol

Abstract: A one-pot reaction of maltol with Lawesson's reagent generates dithiomaltol, a thiopyran-4-thione, via an unusual heterocyclic atom exchange (HCAE) reaction; only pyrones with proton or aliphatic substituents undergo the HCAE substitution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…To obtain the requisite 3HPT compound 10a , the O -methyl protected 3HP 7a was first converted to its thione analog 9 using Lawesson’s reagent. 14 Subsequent BBr 3 deprotection of the methyl ether group yielded the desired compound 10a (Scheme 1). …”
Section: Resultsmentioning
confidence: 99%
“…To obtain the requisite 3HPT compound 10a , the O -methyl protected 3HP 7a was first converted to its thione analog 9 using Lawesson’s reagent. 14 Subsequent BBr 3 deprotection of the methyl ether group yielded the desired compound 10a (Scheme 1). …”
Section: Resultsmentioning
confidence: 99%
“…The conversion of 3-hydroxy-4-pyr(id)ones to the corresponding thionated compounds may be achieved using different strategies and the most common are (i) the addition of 1 eq Lawesson's reagent [49] and (ii) the reaction with an excess of P 4 S 10 [50] under various conditions [51]. The reaction of two equivalents of Lawesson's reagent with 4-pyrones was reported to lead to the formation of dithiopyrones [52].…”
Section: Thio-and Selenopyr(id)onesmentioning
confidence: 99%
“…17,18 A ring substituted derivative, 3-hydroxy-2-methyl-4H-thiopyran-4-thione, dithiomaltol or Httma, was first reported by Brayton, and displayed unusual aromaticity characterized by a downfield shift in the vinylic proton peaks in the 1 H NMR. 19 Recently we reported that the bis-bipyridyl Ru complex of dithiomaltol, [Ru(bpy) 2 (ttma)][PF 6 ] or 1, undergoes C-H activation at a pendant alkyl position upon electrochemical or bulk oxidation, yielding [Ru(bpy) 2 (ttma-alcohol)] + 2 and [Ru(bpy) 2 (ttma-aldehyde)] + 3 as products, Scheme 1. 20 In this report we examine the photo-initiation of similar oxidative reactivity for compound 1 and the homoleptic Zn(ttma) 2 complex, 4, using flash quench methodology, 21 employing electron acceptors 4,4′-dimethyl-1,1′-trimethylene-2,2′dipyridinium (DTDP 2+ ), 1,1′-dimethyl-4,4′-bipyridinium (MV 2+ ), Co(NH 3 ) 5 Cl 2+ , Ru(NH 3 ) 6 3+ , and 2,3-dichloro-5,6-dicyano-1,4benzoquinone (DDQ), Scheme 2.…”
Section: Introductionmentioning
confidence: 99%